Rhetorics and reality: the historiography of British European policy, 1945-73 - Daddow, Oliver J. (2000)
Drawing on postmodern approaches to the practice of history, this thesis examines the historiography of British policy towards European integration since 1945. Its core argument is that historians are subject to a host of pressures. This argument is developed through analysis of seven factors which have influenced the writing of British European policy. Prime amongst them is the influence on historical interpretation of writers' sociological background. The thesis examines the change in the dominant group of writers in the field from politicians to professional historians. It is only in that context, it explains, that the competing interpretations placed on British European policy can be understood. From here, the six other factors at work on writers are examined: the level of analysis writers use to explain British foreign policy, the approach to intentions and outcomes in the international arena, the use of hindsight and empathy in the writing of history, myth-making in contemporary history, the use of sources and the type of study written. The secondary argument advanced in this thesis is that the changing sociological context of the historiography of Britain and Europe can best be elucidated by mapping the writers into schools. Using the typology of historiographical progression set down in American Cold War historiography, the thesis identifies three schools of writing in the historiography of Britain and Europe, 'orthodox', 'revisionist', and 'post-revisionist'. It goes on to draw conclusions about the nature of schools of writing in Britain, drawing particular attention to the comparison with American foreign policy scholarship. The thesis ends by analysing two broader conclusions to emerge from the historiography of Britain and Europe: British historians' obsession with primary sources and implications for the study of the making and implementation of foreign policy. The conclusion also reflects on three broader points of interest: the relationship between questions and answers in history, the lack of attention in methods training courses to the process of narrative construction of historical texts and Britain's continuing inability to define for itself a place in the wider world.